Broccoli Effects on Hif-1 A in Spermatozoa Cells of Ratsthat Induces Psychological Stress (Indian Journal of Forensic Medicine & Toxicology, 2021)
ff
Keywords: Oxidative Stress, Endothelial dysfuction, SFN, Spermatozoa Cells, HIF-1a